Effect of Ignition Location and Vent on Hazards of Indoor Liquefied Petroleum Gas Explosion. Issue 4 (3rd April 2017) - Wang, Yaxing; Lian, Zheng; Zhang, Qi
ABSTRACT: Confined or partially confined gas explosions are one of the major accidents that occur in China. In this study, the effects of ignition location and vent size on the physical processes and the parameters of a propane-air explosion in a vented room were examined using numerical simulation. The peak explosion overpressure for back-wall ignition is significantly higher than that for center ignition. The explosion overpressure for stoichiometric propane-air mixtures in a room without obstacles is too low to cause serious injury. The explosion temperature for stoichiometric propane-air mixtures in a room without obstacles can reach up to 2200 K, which is one of major hazards in a gas explosion in a room. Under the condition of this study, the high temperature gas leaked through the vent can cause injury in a distance up to 38.4 m, which is 8.3 times the length of the room. Maximum peak dynamic pressure is usually reached beyond the vent and has the same order of magnitude with overpressure. The peak dynamic pressure for back ignition is significantly higher than that for center ignition. Both the explosion overpressure in the enclosure and the explosion dynamic pressure beyond the vent for the stoichiometric propane-air mixtures increase as the weak area ratio decreases, in the examined range from 0.1 to 0.4, but the flame region increases with the increase of weak area ratio. For back ignition in the enclosure, the hazard region of explosion high temperature beyond the vent for the stoichiometric propane-air mixtures is largest for α = 0.2.